A New Predictive Equation for Estimating Body Weight in Cirrhotic Patients With Refractory Ascites. (7th June 2021) - Alves, Bruna; da Cruz, Moiséli; Lopes, Antonio; Saueressig, Camila; Dall'Alba, Valesca
Abstract: Objectives: This study aims to develop a new prediction equation to estimate the dry weight (DW) of patients with refractory cirrhotic ascites since there is a lack of evidence to substantiate the current values used to adjust the wet weight in these patients. Methods: Cross-sectional study, that included patients with decompensated cirrhosis undergoing large-volume paracentesis. Height (H) was measured and weight, immediately before and after paracentesis. For the prediction of DW, a linear regression model was performed using as predictor variables: gender, H, and pre-paracentesis weight (preW), as response variable: post-paracentesis weight (postW). Three-way interaction was used to test the joint effect of these predictors. The capacity of this model to predict the postW was evaluated by comparing it with the currently used predictions through the intraclass correlation coefficient (ICC) and the mean square error (MSE). Results: Twenty patients were included, 16 were male. Moderate ascites was the most prevalent grade (n = 18). The mean (range) of ascitic fluid drained was 6.6 (0.45 – 16.0) L, and the difference of Wpre and Wpost was −6.8 (−0.7 – −15.7) kg. The prediction equation developed for estimating DW in male is: DW = −11.4 + 1.2 * Wpre + 0.125 * H −0.002 * Wpre * H, and in female: DW = −40.6 + 1.2 * Wpre + 0.331 * H −0.030 * Wpre * H. ICC values showed that all predictions measures were strongly correlated (r > 0.95). In comparison with current predictions, our model showed the highest ICC (r = 0.97) and the lowest MSE ( = 7.70), comparing with the current predictions (MSE = 18.63, when the preW is adjusted from absolute values and MSE = 12.75 when adjusted from percentage values), indicating more accurate prediction. Conclusions: This new prediction equation showed high reliability as a weight adjustment tool for patients with refractory cirrhotic ascites. Further research is required to validate this prediction equation. Funding Sources: Fundo de Incentivo à Pesquisa e Eventos (FIPE) from Hospital de Clínicas de Porto Alegre and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) from Ministry of Education of Brazil.